Anatomy of the saltgrass (Distichlis spicata L.) leaves with irrigation and without irrigation - Ledea-Rodríguez, José Leonardo; Murillo-Amador, Bernardo; Troyo-Dieguez, Enrique; Nieto-Garibay, Alejandra; Reyes-Pérez, Juan José (Ecosistemas y Recursos Agropecuarios, 2024)
Distichlis spicata is a gramineous halophyte species that grow around the coastal areas. The objective of the study was to identify the modifications in the anatomical structure of stomates of the D. spicata leaf epidermis, cultivated with irrigation and without irrigation conditions. Two populations were selected, 1) plants of D. spicata with irrigation and 2) plants of D. spicata without irrigation. Ten plants per replication were selected from each population, and from each selected plant, the fourth leaf was taken. Each leaf was cut longitudinally into four segments which were dried and analyzed using an Electronic Scanning Microscope. The variables measured were the stomatal density, length, and width of stomates and pores, the stomatal area, the proportion of the pore area concerning the size of the stomata, and the stomata proportion per surface. The results showed that D. spicata populations with irrigation and without irrigation showed anatomical modifications in the structure of stomates in the adaxial epidermis but not in the abaxial epidermis. In the adaxial epidermis, the plants with irrigation showed higher values of stoma length, stoma width, stoma area and pore length, while plants without irrigation showed higher values of proportion pore/stoma and stomatal density. The D. spicata plants without irrigation showed small stomates than plants with irrigation, also, the plants without irrigation, increased the accumulation of salt crystals in the abaxial epidermis.
Keywords: halophytic grass; stomates structures; halophyte species; arid zones